2013
DOI: 10.1039/c3cp44197k
|View full text |Cite
|
Sign up to set email alerts
|

The reaction force constant as an indicator of synchronicity/nonsynchronicity in [4+2] cycloaddition processes

Abstract: A variety of experimental and computational analyses support the concept that a chemical reaction has a transition region, in which the system changes from distorted states of the reactants to distorted states of the products. The boundaries of this region along the intrinsic reaction coordinate ξ, which includes the traditional transition state, are defined unambiguously by the minimum and maximum of the reaction force F(ξ), which is the negative gradient of the potential energy V(ξ). The transition region is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 37 publications
10
73
0
Order By: Relevance
“…It should be noted at this point that in all cases, profiles of relationship between intrinsic reaction coordinate and reaction force constant is different as in the case one-stage one-step reaction, and similar to that in the case of two-stage one-step reaction [37].…”
Section: Quantum Chemical Exploration Of Reaction Pathsmentioning
confidence: 63%
“…It should be noted at this point that in all cases, profiles of relationship between intrinsic reaction coordinate and reaction force constant is different as in the case one-stage one-step reaction, and similar to that in the case of two-stage one-step reaction [37].…”
Section: Quantum Chemical Exploration Of Reaction Pathsmentioning
confidence: 63%
“…It has been demonstrated that the profile of κ(ξ ) in the transition region can be a sensitive diagnostic of mechanistic features, such as the degree of synchronicity in reactions in which several bonds are broken and/or formed [21,30,31]. A fully or nearly fully synchronous process has V(ξ ), F(ξ ) and κ(ξ ) resembling those shown in Figure 1; in particular, κ(ξ ) has just a single minimum between α and γ .…”
Section: Reaction Force Analysismentioning
confidence: 99%
“…A fully or nearly fully synchronous process has V(ξ ), F(ξ ) and κ(ξ ) resembling those shown in Figure 1; in particular, κ(ξ ) has just a single minimum between α and γ . An example is the Diels-Alder reaction between cyclopentadiene and 1,2-dicyanoethylene [31]. However, if there is significant nonsynchronicity, e.g.…”
Section: Reaction Force Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These concepts establish temporal relationships between two chemical events such as the formation/cleavage of chemical bonds and/or electron transfer processes. However, geometric parameters, such as, the (a)symmetry of the bond distances being formed or broken in the transition state (TS), are usually used to ascertain the concertedness and synchronicity of an elementary step . It should be emphasized that relationships between inherently temporal concepts and spatial quantities may not be unique or generally valid.…”
Section: Introductionmentioning
confidence: 99%